Effect of CaCO3 Levels on Formation Phase Material BSCCO-2212 superconductor with Method Mixing Wet - Elsa Mega Puspitaratu; Suprihatin Suprihatin; Pulung Karo karo; Ediman Ginting Suka (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
It has been done a variation of CaCO 3, which is 0.95; 1.00; 1.05; and 1,10, through phase formation of BSCCO-2212 superconductor using a wet-mixing method. Samples were dissolved with HNO 3 and distilled by water slowly until the color was clean blue, then gradually dried out at temperatures of 300, 400, and 600 °C. The samples were calcined for 10 hours at 800°C and sintered at 820°C for 20 hours. The XRD's characterization results show that the highest volume fraction was 76.65% in the Ca 1.05 sample. The lowest volume fraction was 49.85% in the Ca 1.10 sample. Meanwhile, the highest degree of orientation was 44.27% in the Ca 1.00 sample, and the lowest degree of orientation was 8.58% in the Ca 1.10 sample. SEM's characterization shows that all samples have been oriented and relatively little space between slabs (voids).